Elasticidade-renda dos gastos das famílias metropolitanas Brasileiras com transporte urbano e aquisiç\~ao de veículos privados - Carlos Henrique Ribeiro de Carvalho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2014)
– This paper shows how the population has a higher propensity to spend on private transport over public transport as income increases. This analysis is done from calculations of income elasticity of spending on public and on private transport of Brazilian families based on data from the Household Budget Survey of IBGE. Higher income elasticities in spending on private transport indicate more difficulties in the management of traffic and transport for major urban centers in periods of income expansion. Brazil has been experiencing this fact in recent years. The results also show that spending on public transportation has negative elasticity after certain income levels. This fact indicate that there is a lack of attractiveness of these services for the richest families. Aiming at the improvement of mobility and reduction of externalities, the paper discusses some policies that should be adopted to make public transport more attractive compared to private transport and improve the balance of the modal matrix of urban trips.
Keywords: R41; 330; elasticity; transit; urban transportation; families income; transportation families expending